Management of isolated high grade blunt pancreatic injury; case report on lesser aggressive approach - Singh, Manjit; Sarawagi, Mritunjay; Kumar, Anjay; Kumar, Uday (International Surgery Journal, 2019)
Isolated high grade pancreatic injury is rare after blunt abdominal trauma. It is a rare entity to appreciate intra-operatively and a high index of suspicion should always be kept in mind to reach the diagnosis. We are presenting our experience of four cases with moderate to high grade isolated pancreatic injury which were managed in a lesser aggressive approach and had an uneventful outcome.